(untitled) (Quinto Sol, 2018)
This manuscript crosses political history with cultural history. It searches the political and territorial order in Rio Negro Province since its definition about touristic attractive, because that cultural marks become in political ones. This jurisdiction contains one of the most emblematic tourist center: the town of San Carlos de Bariloche and a portion of the Nahuel Huapi National Park. But this area was not taken into account as a scenic reference of the touristic attraction of the Province. The regions presented as the image of Río Negro emerge from politics interest established by the provincial government. The article shows that the political order, and even the citizen construction that was sought to promote in the constitutive period of the province, dialogued and was in based on the specific form of recognition of attractions established since provincial planning, which didn’t take into consideration the Andean space. The internal political construction was focused on other regions. Thus, the attractions were constituted from the political interests established by the provincial government, rather than by the materiality that was promoted.